PENGEMBANGAN MODUL ELEKTRONIK MENGGUNAKAN 3D PAGEFLIP PROFESSIONAL BERBASIS EDMODO PADA MATA PELAJARAN KIMIA - Oktavia, Yessi Rahma; Elvinawati, Elvinawati; Rohiat, Salastri (ALOTROP, 2024)
[The Development of Electronic Module using Edmodo Based-3D Pageflip Professional on Chemistry Subject] This research was an R and D research of developing electronic module using Edmodo-based 3D Pageflip Professional on chemistry subject. The research aimed to determine the feasibility and students’ responses on the developed module. The development process was based of ADDIE model (Analysis, Design, Develop, Implementation, Evaluation). The research was conducted in SMAN 09 (Senior highschool) science class grade IX (MIPA A) on a small scale group of students.. The research results show that (1) the developed product which is the electronic module is feasible as learning material with the feasibility score on media and content were 80,43% and 81,33 % respectively; (2) the students’ response on the module developed show possitive feedback with 80,69% response stated that the module is interesting and helpful in learning chemistry subject.